Rancangan konsep sistem pemantauan dan pengelolaan data produksi berbasis configurable virtual workstation (CVWs) - Andi Arif Isyanto; Sri Raharno (Jurnal Teknik Mesin Indonesia, 2022)
Management of production data that is excessively big and varied is difficult to do manually, so the system that can be used to easily monitor and manage the production data during the process is needed. This study proposes a framework of monitoring and managing production data based on Configurable Virtual Workstation (CVWs) in the rollingstock industry in Indonesia, with a case study of the flat wagon assembly process. The methodology used in this study is by creating a virtual model of assembly elements according to real conditions on the shopfloor. Each of these virtual elements will be connected to each other to get the update information on the shopfloor accurately and transparently to build a cyber-physical system as the first step towards Industry 4.0. Some of the information that can be obtained from the implementations of this system includes: 1) operator working hours; 2) ongoing operation; 3) product completion status; 3) material supply status; 4) product traceability. Based on this information, the actual conditions on the shopfloor can be known and monitored easily and accurately.